Neuroplasticity in the pathogenesis and treatment of chronic pain syndrome: new research and therapeutic perspectives - Lysetskyi, Bohdan; Kobyletskyi, Oleh; Shchybovyk, Dmytro; Zubova, Mariia; Litvin, Olga (Futurity Medicine, 2024)
Recent research and therapeutic outlooks examine the impact of neuroplasticity on the progression and management of chronic pain syndrome. Aims: To review neurobiological basis as well as neuroplastic mechanisms in chronic pain syndrome, exploring bidirectional relationship and innovative therapies and to evaluate efficacy/safety of diverse treatments like TENS, rTMS, pharmacotherapies, and exercise in chronic pain management. Study design: A narrative literature review. Place and Duration of Study: 2019 to 2024. Methodology: A narrative review was conducted using the keywords “Neuroplasticity" AND "Chronic Pain" on PubMed yielded a total of 333 publications. Out of the total publications, 21 were deemed directly relevant, probably providing valuable perspectives on the link between neuroplasticity and chronic pain. Results: Results showed that out of the 11 studies analysed, 7 investigated the bidirectional relationship between chronic pain and neuroplasticity. Additionally, 4 studies reviewed pharmacological methods, 2 studies discussed personalised management and mechanistic profiling, and 7 explored neuromodulation and non-pharmacological interventions. Various neurophysiological correlates of chronic pain were studied, including somatosensory and cortical neurophysiology profiles but Central sensitisation and neuroinflammation were the explored key mechanisms. Activity-dependent plasticity, neuroplasticity in pain modulation, and cortical plasticity are extensively explored, revealing changes in neural activity, synaptic strength, and brain structure. Research explores the connection between chronic pain and neuroplasticity, examining how they impact each other and highlighting the constant interaction between pain perception and neural plasticity. Innovative therapeutic strategies include neuromodulation techniques, pharmacological interventions, personalised pain management, and multimodal approach. Non-invasive brain stimulation, transcutaneous electrical nerve stimulation , and home-based focused tDCS show promise in chronic pain management. Conclusion: In summary, these findings highlighted the multifaceted nature of chronic pain and the on-going efforts to develop effective therapeutic interventions, showcasing a dynamic field of research aiming to improve the lives of those suffering from chronic pain.